Does obesity associate with mortality among hispanic persons? Results from the national health interview survey. (17th April 2013) - Mehta, Tapan; McCubrey, Raymond; Pajewski, Nicholas M.; Keith, Scott W.; Allison, David B.; Crespo, Carlos J.; Fontaine, Kevin R.
Abstract : Objective: To evaluate the association between BMI: kg/m 2 and mortality among Hispanic adults. Design and Methods: Eight years (1997‐2004) of National Health Interview Survey data linked to public‐use mortality follow‐up data through 2006 were acquired. Using Cox proportional hazards regression, separate models for two attained age strata (18 to <60 years, ≥60 years) adjusting for sex, smoking, and physical activity with over 38, 000 analyzable respondents were fit. Results: Among those aged ≥60 years, underweight (BMI ≤ 18.5) associated with elevated mortality (hazard ratio [HR] = 2.19; 95% confidence interval [CI], 1.38‐3.46), whereas overweight (BMI of 25 to <30) and obesity grade 1 (BMI of 30 to <35) associated with reduced mortality (HRs = 0.79; 95% CI, 0.65‐0.95 and 0.71; 95% CI, 0.56‐0.91), respectively. There were no significant associations between BMI and mortality among the 18 to <60 years attained age strata or among never smokers for either age strata. Conclusions: Overweight and obesity are not obviously associated with elevated mortality among Hispanic adults.